KAJIAN KRITIS TENTANG AKULTURASI ISLAM DAN BUDAYA LOKAL - M. Arsad AT (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2012)
Islam came to archipelago (Indonesia) could not be separated from the shades where Islam was born. However, Islam that was brought to Indonesia adapted with the local culture. The process of compounding between Islamization and acculturation, made Islam in the archipelago easily accepted by society. There is no resistance, except reception. If there is a modifications, it is no more than the injection of Islamic values in a tradition that have been there. In its development, the Islamic archipelago with moderate characteristics, local culture appreciation, and taking sides to local residents in facing the challenge, causing Islam was accepted as a new religion. The real proof of the compounds between Islam and local culture, can be found in the work of the Chronicle, saga, lontara, literature, mysticism, mythology. Then, in terms of the architecture of the nineth layered roof buildings of the mosque of Demak